Evaluation of Safety Awareness Among Workers Related to Physical Injury Accident in Manufacturing Industry - Abdul Halim, Aiman Hazib; Aliff Hisyam A Razak (Progress in Engineering Application and Technology, 2023)
Factors contributing to workplace accident due to lack of safety awareness was investigated. The main objective of this study is to investigate the level of safety awareness among employees and to analyze the association of hazard and policies towards safety awareness among workers in the manufacturing industry using statistical method. Two hypotheses in this study are namely workplace hazard versus workplace policy, and procedure. Method to assess the awareness of workplace safety among workers is via questionnaires. The data collection was conducted at Continental Alor Setar, Kedah. Continental Alor Setar produces tires for vehicles such as motorcycles, cars and trucks. The respondents are among the workers in the production department and the sample size is 50 workers. The Statistical Package for the Social Science (SPSS) was used to analyze the data. The results of the study found that the level of safety awareness among employees is at moderate level. In addition, this study found that workplace hazards are not in line with workplace policy and procedure. For future study, an alternative way can be studied to increase the level of safety awareness among workers in the manufacturing sector in order to reducing number of accidents.